PENGENALAN JENIS SAMPAH LAUT DAN METODE PENGELOLAANNYA BERBASIS ECOBRICKS BAGI SISWA SEKOLAH MINGGU - Novianty Tuhumury; Juliana W. Tuahatu; Gratia D. Manuputty (Universitas Mataram, 2023)
Knowledge about waste, pollution, and its impacts is a crucial issue to provide in society, and it is important to instill this in children because their characteristic is easier to build. The impact of pollution will be experienced by any generation whether in a short or long term period. A simple and practical method to manage waste, especially plastic, is by making eco-bricks. It is an easy way to practice. The community service activity aims to introduce marine debris and plastic waste management concept based on eco-bricks for Sunday School students. The activity was carried out on Thursday, April 20, 2023, involving the students from Sunday School Service students which was located in Airlouw Village Ambon. The methods were demonstration, training, lecture, and evaluation by providing questions regarding pollution and how to deal with it. The participants were divided into groups, assigned to complete a scheme of waste fate in the environment from human activities to its effects on waters and humans themselves, trained to handle plastic waste by making eco-bricks, and equipped with knowledge related to types of waste and its degradation process. Although only some participants were familiar with eco-bricks-based waste processing, all participants are easy to implement the process. The accomplishment can be directly measured through the discussion process carried out simultaneously during the training process. All in all, education complemented by material enrichment and schematic assignments can train children’s thinking skills, and practical method for managing waste is weighty for a young age.